1960
DOI: 10.1139/z60-112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Densities and Periods of Infestation on the Growth-Forms of a Host and Parasite Population

Abstract: Initial densities and periods of infestation of adults of Trialeurodes vaporariorum and its chalcid parasite Encarsia formosa influence subsequent fluctuations in numbers of adults of both host and parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
17
1
Order By: Relevance
“…Secondarily, E. formosa's interaction with T. vaporariorum has also been modeled in an attempt to identify factors that stabilize such interactions (14,16,17,165,170,171). Factors affecting population dynamics of E. formosa and T. vaporariorum in greenhouse vegetable systems include hostparasitoid ratios, starting density and age structure of whitefly populations at time of first parasitoid releases (17, 31), levels of host-feeding and parasitism (18), temperature, and host plant (98).…”
Section: Host/parasitoid Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondarily, E. formosa's interaction with T. vaporariorum has also been modeled in an attempt to identify factors that stabilize such interactions (14,16,17,165,170,171). Factors affecting population dynamics of E. formosa and T. vaporariorum in greenhouse vegetable systems include hostparasitoid ratios, starting density and age structure of whitefly populations at time of first parasitoid releases (17, 31), levels of host-feeding and parasitism (18), temperature, and host plant (98).…”
Section: Host/parasitoid Dynamicsmentioning
confidence: 99%
“…Burnett studied E. formosa's interaction with T. vaporariorum (14,16) and found that initial whitefly density (17) and the interaction between host-feeding and whitefly population age structure (18) strongly influenced the dynamic outcome. Van Lenteren et al (131) concluded that multiple introductions of E. formosa over a 16-week period were necessary to stabilize E. formosa-T. vaporariorum population fluctuations on greenhouse tomatoes.…”
Section: Host/parasitoid Dynamicsmentioning
confidence: 99%
“…The threshold conditions which guarantee that the pest dies out are derived, and several governing factors including application timing and control tactics are investigated with regard to the extent of depression or resurgence resulting from pulses of pesticide applications. Experimental observations have shown that the initial densities of pest and natural enemy populations can affect classical biological control (Burnett, 1960;Foster and Kelly, 1978;Jones, 1999). The numerical results obtained in the present paper also indicate that the simplest pest-natural enemy models with impulsive control tactics can lead to the coexistence of pests and natural enemies for a wide range of parameters, but with quite different pest amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Milliron (1943) published a detailed life history of the greenhouse whitefly and E. formosa. Subsequently Burnett (1949Burnett ( , 1960Burnett ( , 1967 described the effect of temperature and other factors on the interaction between these two organisms. ~u m e t t showed that both temperature and proportion of parasite to host were critical factors in the final outcome of a relatively long-term host-parasite system.…”
Section: Introductionmentioning
confidence: 99%